Deep Brain Stimulation for Multiple Sclerosis Tremor: A Meta‐Analysis. Issue 4 (22nd November 2019) - Brandmeir, Nicholas J.; Murray, Ann; Cheyuo, Cletus; Ferari, Christopher; Rezai, Ali R.
Abstract : Objectives: To examine the effect of deep brain stimulation (DBS) on multiple sclerosis (MS)‐tremor, as measured by a normalized scale of tremor severity, with a meta‐analysis of the published literature. Methods: Medline and EBSCO Host (January, 1998 to June, 2018) were systematically reviewed with librarian guidance, using the keywords "Deep brain stimulation" and "multiple sclerosis." Bibliographies and experts in the field were also consulted to identify missed articles. All therapeutic studies on DBS for MS‐tremor, reported in the English language, within the study period were included. Papers that reported outcomes without a measure of central tendency and/or distribution were excluded. The papers were read in their entirety and graded for risk of bias according to the American Academy of Neurology (AAN) standards. To maximize statistical power, papers using different stimulation targets were grouped together. Outcomes were reported with the Fahn‐Tolosa‐Marin scale (FTM), the Bain‐Finchley scale (CRS) and 3‐ and 4‐point tremor severity scales and normalized with a Hedges g. Results: The search produced 13 studies suitable for meta‐analysis. The random‐effects meta‐analysis showed that DBS improved the Hedges standardized mean tremor score by 2.86 (95%CI 2.03–3.70, p < .00001). Heterogeneity was high, with an I 2 of 84%, suggesting that random effects model is more appropriate. Adverse event rates varied from 8% to 50%. Conclusions: This meta‐analysis provides level III evidence that DBS may improve MS‐related tremor as measured by standardized tremor severity scales.